Risk Factor of Preeclampsia in a Secondary Indonesian Hospital: A Case-Control Study - Lady Aqnes Kurniawati; Muhammad Ilham Aldika Akbar; Budi Utomo; Aditiawarman (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Preeclampsia is a form of hypertension in pregnancy that leads to morbidity and mortality.Although the etiology remains unclear, there are some risk factors that are suspected to be associated withthe development ofpreeclampsia. Objective: To find out the risk factors associated with the incidence ofpreeclampsia inAirlangga University Hospital. Method: This studyconducted an analytical-observationalstudy with the hospitalized unmatchedbased case-control approach. 165 pregnant women were included.Data were analyzed in univariate, bivariate, and multivariate regression logistic and performed usingstatistical package for the social science (SPSS), p < 0.05 was considered statistically significant. Results:Pregnant women with preeclampsia were about 18 to 44 years old, with the average BMIis 31.19 kg/m2.There are significant relation between family history of hypertension (p = 0.000), maternal age (p = 0.004),BMI (p = 0.000), pregnancy interval (p = 0.009), and chronic hypertension (p = 0.007) with the incidenceof preeclampsia. In the multivariate analysis using logistic regression, family history of hypertension wasthe most dominant factor with OR: 3.374 and 95% CI: 1.454 – 7.830 compared to other factors such asmaternal age (OR: 2.885; 95% CI: 1.311 – 6.347; p: 0.008) , and BMI (OR: 2.590; 95% CI: 1.525 – 4.400;p: 0.000). Conclusion: Family history of hypertension, maternal age, BMI, pregnancy interval, and chronichypertension have a significant relationship with the incidence of preeclampsia. In multivariate analysis,family history of hypertension is the most dominant risk factor among others.